Innovations in the selection program of the UPRA-Grupo Pastores in Rasa aragonesa sheep breed - Riaguas L.; Fantova E.; Equipo Veterinario Oviaragón Grupo Pastores; Calvo J.H.; Alabart J.L.; Folch J.; Lahoz B.; Jurado J.J.; Jiménez M.A.; Serrano M. (Innovation for sustainability in sheep and goats, 2019)
The Cooperative Oviaragón-Grupo Pastores carries out since 1994 a selection program for prolificacy in Rasa Aragonesa sheep, with 490,337 ewes at present. Sires of higher estimated breeding values are produced within the scheme by MOET, increasing the performance of this technology through the measurement of plasmatic Anti-Müllerian Hormone (AMH) in ewe embryo donors, an endocrine marker of the ovarian activity. Within this program a natural genetic prolific variant was found in 2007, the FecXR allele of the BMP15 gene. Its effect on prolificacy leads to an increase of 0.35 lambs/lambing ewe when compared with non-carrier ewes, with an additive effect over the standard hormonal treatments used in farms. Recently, new variants in MTNR1A gene associated to reproductive seasonality have been detected in Rasa aragonesa breed. Non-linked SNPs in the promoter and exon 2 have been detected which decrease the length of the non-cycling period (periods with three or more consecutive weekly-sampled progesterone concentrations lower than 0.5 ng/ml from January to August) as much as 30 and 53 days, respectively. In the same way, the allele located in exon 2 was also associated to an increase of 15% of oestrus cycling months (based on oestrus records). Due to their productive interest, a controlled program for the outreach of FecXR and MTNR1A alleles has been developed. Finally, a polygenic selection program for maternal capacity is being carried out. The selection program goes on with a combined polygenic selection for prolificacy, maternal capacity and dissemination of FecXR and MTNR1A alleles.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)